Development of nanoemulsion containing kojic acid ester for cosmeceutical application - Syed Azhar, Sharifah Nurfadhlin Afifah (2018)
Kojic acid (KA) and its derivatives such as kojic acid ester (KAE) are well-known tyrosinase inhibitor that widely used in food and cosmetic industries. The antityrosinase properties of these compounds known to be effective in the treatment of overproduction of melanin such as hyperpigmentation for cosmeceutical applications. Kojic acid ester was used as the active ingredient and encapsulated in the nanoemulsion system. To design excellent formulation, the nanoemulsion containing kojic acid ester (KAE) was screened with different level of variables by using D-optimal experimental mixture design (MED), solubility determination in various oils and finally the preparation system was further developed. DOptimal Mixture Experimental Design (MED) was used for optimizing the composition of nanoemulsions suitable for topical delivery system. The optimized nanoemulsion containing kojic acid ester with desirable criteria was 10.00 % w/w of KAE, 3.19 % w/w of T80, 3.74 % w/w of castor oil: lemon essential oil (ratio 9: 1), 0.70 % w/w of xanthan gum and 81.68 % w/w of deionized water. This optimum nanoemulsion containing KAE showed suitable agreement between the actual droplet size (110.01 nm) and the predicted droplet size (111.73 nm). The residual standard error (RSE) value of nanoemulsion containing KAE was less than 2.0%. The optimized nanoemulsion containing KAE with pH value of 6.28 showed high conductivity value (1492.00 μScmˉ1) indicated that oil-in-water nanoemulsion was obtained. The nanoemulsion remained stable (no phase separation was observed) under accelerated stability during storage at 4°C, 25°C and 45°C within 90 days, centrifugal force as well as freeze-thaw cycles. Rheology measurement justified that the optimized nanoemulsion containing KAE was more elastic (shear thinning and pseudoplastic properties) rather than viscous characteristics. The permeation study showed that the permeability of KAE was significantly improved and the release increased from 4.94% at 1 h to 59.64% at 8 h of application. The permeation rate of nanoemulsion containing KAE at 8 h was 4659.50 μg.cm-2. h- 1 (initial concentration, Co = 2000 μg/mL) with permeability coefficient (Kp) value of 0.48 cm.h-1. Antimicrobial activity of nanoemulsion containing KAE was studied against the skin pathogen bacteria called Staphylococcus aureus ATCC 43300. The results indicated that the inhibition zone size of the optimized nanoemulsion containing KAE (8.00 mm) was slightly bigger than KAE oil (6.5 mm). In vitro cytotoxicity of the optimized nanoemulsion containing KAE and KAE were tested using fibroblast cell line (3T3). The IC50 (50% inhibition of cell viability) of nanoemulsion containing KAE was more than 100 μg/mL. The survival rate of 3T3 cell on nanoemulsion containing KAE (54.76 %) was found to be higher compared to KAE (53.37 %) without any toxicity sign. The in vivo toxicity effect on zebrafish embryos (Danio rerio) was also investigated. The calculated LC50 (50% lethal concentration) values of nanoemulsion containing KAE showed no toxicity effect with more than 500 μg/mL. Nanoemulsion containing KAE proved to be less toxic and can be applied for cosmeceutical applications. This study has revealed that kojic acid ester could be developed as a new active ingredient with nanoemulsion based system and have a potential to be used for further cosmeceutical applications.